IUTAM Symposium on Recent Advances of Acoustic Waves in Solids Proceedings of the IUTAM Symposium on Recent Advances of Acoustic Waves in Solids, Taipei, Taiwan, May 25-28, 2009 - Wu, Tsung-Tsong.; Ma, Chien-Ching.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Rapid growth of the mobile communication market has triggered extensive research on the bulk as well as surface acoustic wave devices in the last decade. Quite a few important results on the modeling and simulation of Film Bulk Acoustic Resonator (FBAR) and Layered SAW devices were reported recently. The other recent advance of acoustic waves in solids is the so-called phononic crystals or phononic band-gap materials. Analogous to the band-gap of light in photonic crystals, acoustic waves in periodic elastic structures also exhibit band-gap. Important applications of phononic band gap materials can potentially be found with creating a vibration free environment in microstructures, and design of advanced acoustic frequency filter, etc. In addition to the wave electronics and phononic crystals, to facilitate the emerging needs in the quantitative nondestructive evaluation of materials, waves in anisotropic solids and/or electro-, magneto- interaction problems also regained much attention recently. Topics treated include: Waves in piezoelectric crystals; Simulation of advanced BAW and SAW devices; Analysis of band gaps in phononic structures; Experimental investigation of phononic structures; Waves in multilayered media;Waves in anisotropic solids and/or electro-, magneto-interaction problems.
WAVES IN GENERAL -- Existence of Exceptional Body Waves and Subsonic Surface Waves in Monoclinic and Orthotropic Materials -- Deformation Waves in Microstructured Materials: Theory and Numerics -- WAVES AND NDE -- Generation and Propagation of Anti-Plane Surface Waves on a Body with Depth-Dependent Properties -- Resonance Ultrasound Microscopy for Imaging Young$1 (Bs Modulus of Solids -- Non-Classical Nonlinearity in Solids for Defect-Selective Imaging and NDE -- Counterpropagating Ultrasonic Waves for Inhomogeneous Materials Characterization -- Ultrasonic Characterization of the Mechanical Properties of Thin Films and Coatings -- Evaluation of Corrosion in Carbon Steel Pipes by Laser-Generated Guided Wave -- Measurement of Surface and Lamb Waves with Application on Acoustic Sensing and Non-Destructive Evaluation -- PHONONIC CRYSTALS -- Guided Elastic Waves at Periodically Structured Surfaces and Interfaces -- Acoustic Cloaking by Metafluids -- Band Structure and Phonon Transport in a Phononic Crystal Made of a Periodic Array of Dots on a Membrane -- Material Parameters Determining the Band Gaps of Solid-Solid Phononic Crystals -- Behavior of Wave Motion in an Acoustic Metamaterial with Anisotropic Mass Density -- Complex Band Structure of Phononic Crystals and the Diffraction Problem -- Versatile Phononic Slabs -- Omnidirectional Band Gap Mirror for Surface Acoustic Wave -- Band Structure of Three-Dimensional Phononic Crystals with an Opal Structure -- Bandgap Characteristics of a 3D Phononic Meta Material Composed of Ordered Quantum Dots -- Analytical and Experimental Analysis of Bandgaps in Nonlinear one Dimensional Periodic Structures -- Lamb Waves in Phononic-Crystal Plates: Numerical Studies and Experiments -- WAVE ELECTRONICS -- Phase-Sensitive and Fast-Scanning Laser Probe System for RF SAW/BAW Devices -- A Two-Dimensional Analysis of Surface Acoustic Waves in Finite Piezoelectric Plates -- Wireless Drive of Piezoelectric Components -- Novel High Frequency, Temperature Stable, Quartz Gyroscopes -- COM Model Characterization for RF SAW Devices -- Propagation Characteristics of Surface Acoustic Wave and Properties of Gas Sensors on Quartz -- Three Dimensional Displacement Measurement of Transient Elastic Wave Propagation Using a Multidimensional Point-Wise Fiber Bragg Grating Displacement Sensor System -- SEMINAR SECTION -- Band Structure Calculations by Modal Analysis -- Band Gap in Phononic Crystal Thin Plate with/without Mirror Plane -- Radial Sonic Crystals -- Polarization States in 2D Phononic Crystals and Phononic Crystal Waveguides -- Dispersion Analysis of Wave Motion in Microstructured Solids -- On the Role that Scholte Waves Play in Acoustic Propagation along a Fluid-Solid Interface -- Forced Motions in Rectangular Elastic Waveguide -- Normal Waves in Anisotropic Cylinders of Sector Cross-Section -- Dispersion Behaviors of ASF Modes Propagating along Wedges Tips with Coatings -- Scattering from a Rectangular Crack in a Cladding -- Defect Inspection of Complex Structure in Pipes by Guided Waves -- SAW Gas Sensor with Nanostructured Sensing Materials -- Design of IF Two-Track Surface Acoustic Wave Filters Using (100) AlN/Diamond Structures -- Acoustic Wave Properties of (100) AlN Films -- Probing Viscoelastic Properties of Polymer Solution Boundary Layers Using Quartz Crystal Resonator.s
Keywords: Acoustics; Engineering; Mechanics, applied; Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Acoustics; Computational Intelligence; Engineering, general; Theoretical and Applied Mechanics